2015
DOI: 10.1002/2015jb011968
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic sealing due to pressure solution contact zone growth in siliciclastic rock fractures

Abstract: Thermo‐hydro‐mechanical‐chemical simulations at the pore scale are conducted to study the hydraulic sealing of siliciclastic rock fractures as contact zones grow driven by pressure dissolution. The evolving fluid‐saturated three‐dimensional pore space of the fracture results from the elastic contact between self‐affine, randomly rough surfaces in response to the effective confining pressure. A diffusion‐reaction equation controls pressure solution over contact zones as a function of their emergent geometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 75 publications
0
36
0
Order By: Relevance
“…Many factors can affect the magnitude of permeability of fractured rock masses, including fracture length [28][29][30][31], aperture [32][33][34], surface roughness [35,36], dead-end [37], number of intersections [38,39], hydraulic gradient [40], boundary stress [41,42], anisotropy [43][44][45][46], scale [47][48][49][50], stiffness [51], coupled thermo-hydro-mechanical-chemical (HTMC) processes [52][53][54][55], and precipitation-dissolution and biogeochemistry [56]. The discrete fracture network (DFN) model, which can consider most of the above parameters, has been increasingly utilized to simulate fluid flow in the complex 2 Geofluids fractured rock masses [57][58][59][60], although it cannot model the aperture heterogeneity of each fracture [61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can affect the magnitude of permeability of fractured rock masses, including fracture length [28][29][30][31], aperture [32][33][34], surface roughness [35,36], dead-end [37], number of intersections [38,39], hydraulic gradient [40], boundary stress [41,42], anisotropy [43][44][45][46], scale [47][48][49][50], stiffness [51], coupled thermo-hydro-mechanical-chemical (HTMC) processes [52][53][54][55], and precipitation-dissolution and biogeochemistry [56]. The discrete fracture network (DFN) model, which can consider most of the above parameters, has been increasingly utilized to simulate fluid flow in the complex 2 Geofluids fractured rock masses [57][58][59][60], although it cannot model the aperture heterogeneity of each fracture [61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure dissolution model is based on a closed-form approximation to a reaction-diffusion equation in a water-quartz environment for spherical contacts (Lehner and Leroy, 2004;Bernabé and Evans, 2007), extended to arbitrarily shaped contacts (Lang et al, 2015):…”
Section: Methodsmentioning
confidence: 99%
“…Building on previous work (Lang et al, 2015), the present study presents coupled hydro-mechanical-chemical simulations at the pore scale to assess changes in fracture normal stiffness under the effects of pressure solution and precipitation, for a water-quartz system. Specifically, instantaneous fracture closure curves are generated, for specific points in time during the dissolution and precipitation process, and related to changes in the rock surface morphology ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that pure normal loading may not be the main reason for the fast closure of a fracture, and the damages of contact between the two walls of a fracture during normal loading play an important role. Lang et al 43 simulated the hydraulic sealing due to pressure solution in siliciclastic rock fractures. Their results show that under pressure solution, the contact zone grows and leads to flow channeling.…”
Section: Introductionmentioning
confidence: 99%